Verification of a method for determining the length of spinal fixation during ventral corrective spinal fusion - Petrenko, Dmytro; Mezentsev, Andrey; Demchenko, Oleksandr; Barkov, Oleksandr (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2013)
The paper presents results of verification and evaluation of capabilities of a method for determining the length of spinal fixation during ventral corrective spinal fusion in patients with idiopathic scoliosis. The study was conducted by two stages. At the first one, criteria of consistency and reproducibility between experts in their study of radiographs of 30 patients with idiopathic scoliosis were determined. Clinical verification of the method for determining the length of ventral corrective spinal fusion was carried out at the second stage. It was revealed that the suggested method had a good degree of consistency and an excellent one of reproducibility, and its use provided a satisfactory clinical outcome.